1983
DOI: 10.1111/j.1399-6576.1983.tb01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Response to the Clinical Use of Alpha Adrenergic Receptor Blocking Agents

Abstract: Treatment with alpha adrenergic receptor blocking agents has been used clinically for many years to obviate peripheral vasoconstriction in patients suffering from circulatory or thermoregulatory distress. Various reports indicating that administration of these agents may be followed by an increased plasma concentration of catecholamines, and subsequently an increased oxygen demand, led to 29 investigations on humans who were placed in a horizontal position in a thermoneutral environment and given 25 mg chlorpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The neuroleptics used may affect plasma NE and 3‐MT levels. Previous clinical study has indicated that haloperidol (5‐10 mg/day or 10‐20 mg/day) decreased plasma NE levels in schizophrenics over a 6‐week course of treatment,29 and that infusion of chlorpromazine (25 mg) decreased plasma NE levels 30. However, a number of studies have found that the neuroleptics have no effect on peripheral NE levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroleptics used may affect plasma NE and 3‐MT levels. Previous clinical study has indicated that haloperidol (5‐10 mg/day or 10‐20 mg/day) decreased plasma NE levels in schizophrenics over a 6‐week course of treatment,29 and that infusion of chlorpromazine (25 mg) decreased plasma NE levels 30. However, a number of studies have found that the neuroleptics have no effect on peripheral NE levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical study has indicated that haloperidol (5-10 mg/day or 10-20 mg/day) decreased plasma NE levels in schizophrenics over a 6-week course of treatment, 29 and that infusion of chlorpromazine (25 mg) decreased plasma NE levels. 30 However, a number of studies have found that the neuroleptics have no effect on peripheral NE levels. Haloperidol (4 mg/day) for 5 weeks, 31 or administration of haloperidol (4-8 mg/ day) or thioridazine (150-400 mg/day) for at least 10 days, 32 has no significant effect on peripheral noradrenergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that haloperidol 22 or chlorpromazine 23 decreased plasma NE levels, and that thioridazine 24 had no significant effect on peripheral noradrenergic activity. Preclinical studies have reported that haloperidol or chlorpromazine had no significant effects on brain 3-MT levels.…”
Section: Increased Sensitivity To Stress Associated With a Predominanmentioning
confidence: 99%
“…Treatment with haloperidol (4-8 mg / day) or thioridazine (150-400 mg / day) for at least 10 days has been reported to have no effect on peripheral noradrenergic activity (Tuck 1973). Infusion of chlorpromazine (25 mg) has been shown to decrease plasma NE levels (Risbo et al 1983). In the present study, both the 13 medicated and the 13 later-medicated subjects with flashbacks had significantly higher NE levels than the user and non-user controls.…”
Section: Discussionmentioning
confidence: 98%